KAJIAN WARNA BUAH DAN UKURAN BENIH TERHADAP VIABILITAS BENIH KOPI ARABIKA (Coffea arabica L.) VARIETAS GAYO 1 - Cut Nur Ichsan Nur Ichsan; Agam Ihsan Hereri; Lina Budiarti (Jurnal Floratek, 2013)
ABSTRACT The purpose of this study was to examine seed viabilities of Arabica Coffee, variety Gayo 1 which was different in color of the fruits and in size of the seeds. The study was also aimed at examining interactions between fruit color and seed size on seed viabilities. Experiment was arranged in a randomized complete block design with three replications.  Factors studied were 1) fruit color consisted of three levels, namely, bright red, dark red, and yellowish green and 2) seed size consisted of large seeds, medium, small. Results showed that fruit color significantly affected germination rate, seedling growth rate, prompt germination, the time required to reach 50% germination (T50) and dry weight of normal seedlings. Seed size significantly affected germination rate, seedling growth rate, prompt germination, T50, and dry weight of normal seedlings. The best viability was found in the seeds derived from bright red fruits and small sized seeds.